Enforced sojourn: Zimbabwean dispensation, special and exemption permits - Maziyanhanga, Zvikomborero (Rhodes University, Faculty of Humanities, Department of Political and International Studies)
This thesis investigates Zimbabwean's immigration to South Africa. Zimbabwean's immigration to South Africa dates back to the early 2000s. This thesis uses a combination of theories to interrogate and discuss the Zimbabwe special permits and some of the post-apartheid government's amendments to the South African Citizenship Act and other immigration policies. Some of the theories that theoretically underpin this research project's methodology include Marxism, Pan-Africanism, Liberalism and culture-based theories. This thesis interrogates the discursive strategies these permits draw on to frame and understand Zimbabwean immigrants in South Africa. This study has found that these permits use similar operating logic as the White South African governments used the migrant labour system to exploit Blacks from all of Southern Africa in the 20th century. For instance, the migrant labour system used during apartheid made all Blacks in South Africa "guest workers" who could be deported at the government's whim. The apartheid government used racist pass laws to regulate the movement of Black people in South Africa, whereas the post-apartheid government uses Zimbabwean special permits to regulate the movement of Zimbabweans in South Africa. The pass laws were fundamentally racist, and their ultimate objective was to reinforce the idea of White citizenship, whereas the Zimbabwe special permits are not racist. Their colonial similarity, however, lies in how they make Zimbabwean migrants perpetual migrants in South Africa and the various ways in which they cast Zimbabweans as not deserving of South African citizenship. These special permits force Zimbabwe migrants to become "guest workers" who build the post-apartheid economy and then return home when they are no longer "useful" to the economy. This thesis concludes that the post-apartheid Zimbabwe special permits achieve analogous objectives.
Keywords: Citizenship; Immigrants -- South Africa; Residence permit; Foreign workers, Zimbabwean -- South Africa; Discrimination; Emigration and immigration law -- South Africa